A CASE STUDY AT COMPANY X ON DETERMINING SELLING PRICE BASED ON COST PLUS PRICING - Sofyan, Ihsanul Alvin (Jurnal Ilmiah Mahasiswa FEB, 2020)
In a company that mainly use machinary as labor in processing a product, determining the selling price can be tricky, due to the large number of expenses that will be the determining factor of the selling price, which the expenses cover machine maintenance, repair, depreciation, etc. Company X only apply expenses data that is directly shared evently by all the products they produce, where this action can increase or reduce the selling price in an inaccurate way. Therefore, the writer will calculate the selling price determination using the Cost-Plus Pricing method and determine the cost of goods sold using the Process Costing method which is found by the author to be more suitable for Company X. The emergence of the ASIA free market has also affected mining companies, due to the many products imported to Indonesia market has a selling price that is much lower than the average market price in Indonesia that causing customers loss, therefore in addition to maximizing the accuracy of production calculations and product selling prices, researchers will also try to maintain the selling price in order to remain able to compete and / or give an opportunity to make new customers.Keyword: Process Costing, Cost-Plus Pricing, Mineral Processing Company.